Vaccine Hesitancy and Support for Employer Vaccine Mandates - Ashwell, Douglas; Cullinane, Joanna; Croucher, Stephen M (Frontiers in Communication, 2021)
This study investigated COVID-19 vaccine hesitancy and support for employer vaccine mandates and support for termination for non-vaccinated employees among a national sample in New Zealand. A total of 1852 individuals participated in the study. Results indicated participants who are able to get vaccinated are less likely to support employer mandated vaccinations and the rights of employers to terminate employees who refuse to get vaccinated. However, individuals who self-identify that they can get vaccinated and have higher confidence in the COVID-19 vaccine are more likely to get vaccinated. Age and confidence in the vaccine influence support for mandates, while age and political affiliation influenced support for employer right to terminate a non-vaccinated employee. Understanding support, or lack thereof, for such initiatives is essential as businesses and nations respond to growing COVID concerns.